KONSEP HUNIAN KELAS ATAS DALAM TAYANGAN PROPERTY ADVERTISING AGUNG SEDAYU GROUP DI TELEVISI - Murfianti, Fitri (Seni Media Rekam ISI Surakarta, 2010)
The Advertisement of Agung Sedayu Group is a representation the high class property. This will have a strong correlation between symbols and power and authority implicitly or even explicitly. The housing that is shown not only the place of living but also the realization of the concept of ‘one stop living’Keyword: representation, property advertising, one stop living